1991
DOI: 10.1128/jb.173.17.5554-5557.1991
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Escherichia coli TonB membrane topology by use of PhoA fusions

Abstract: Alkaline phosphatase (PhoA) fusions to TonB amino acids 32, 60, 125, 207, and 239 (the carboxy terminus) all showed high PhoA activity; a PhoA fusion to TonB amino acid 12 was inactive. The full-length TonB-PhoA fusion protein was associated with the cytoplasmic membrane and retained partial TonB function. These results support a model in which TonB is anchored in the cytoplasmic membrane by its hydrophobic amino terminus, with the remainder of the protein, including its hydrophobic carboxy terminus, extending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 21 publications
0
75
1
Order By: Relevance
“…Since TonB has been demonstrated to interact physically with ExbB (20,32) and since TonB and ExbD have similar topologies (12,15,29), we wanted to determine whether TonB-ExbD interactions could be further characterized. Unfortunately, neither in vivo cross-linking nor competition studies with ExbD-PhoA revealed any interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Since TonB has been demonstrated to interact physically with ExbB (20,32) and since TonB and ExbD have similar topologies (12,15,29), we wanted to determine whether TonB-ExbD interactions could be further characterized. Unfortunately, neither in vivo cross-linking nor competition studies with ExbD-PhoA revealed any interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out primarily in Escherichia coli indicate that the receptors form gated pores in the outer membrane, and iron transport via these receptors requires TonB, ExbB and ExbD (Klebba et al, 1993). TonB is a periplasmic protein that is anchored in the cytoplasmic membrane by its hydrophobic N-terminal amino acids (Postle and Skare, 1988;Skare et al, 1989;Roof et al, 1991). TonB is associated with two accessory proteins, ExbB and ExbD.…”
Section: Introductionmentioning
confidence: 99%
“…TonB protein is anchored in the cytoplasmic membrane by its uncleaved N-terminus, which serves as a signal anchor (Postle and Skare, 1988;Roof et al, 1991;Skare et al, 1989), a probable connection to the pmf (Jaskula et al, 1994), and a region of contact with one of the three transmembrane domains of ExbB (Karlsson et al, 1993a;Larsen et al, 1994;Traub et al, 1993). Although TonB has been localized to the cytoplasmic membrane by several groups (Hannavy et al, 1990;Plastow and Holland, 1979;Roof et al, 1991), its association with the outer membrane has never been investigated even though there have been numerous suggestions that such an interaction takes place (Bell et al, 1990;Braun et al, 1991;GĂĽ nter and Braun, 1990;Reynolds et al, 1980;Schö ffler and Braun, 1989;Tuckman and Osburne, 1992), including the detection, by in vivo cross-linking, of direct physical interaction with the outer membrane receptor FepA (Skare et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Although TonB has been localized to the cytoplasmic membrane by several groups (Hannavy et al, 1990;Plastow and Holland, 1979;Roof et al, 1991), its association with the outer membrane has never been investigated even though there have been numerous suggestions that such an interaction takes place (Bell et al, 1990;Braun et al, 1991;GĂĽ nter and Braun, 1990;Reynolds et al, 1980;Schö ffler and Braun, 1989;Tuckman and Osburne, 1992), including the detection, by in vivo cross-linking, of direct physical interaction with the outer membrane receptor FepA (Skare et al, 1993).…”
Section: Introductionmentioning
confidence: 99%